PENGARUH RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), DAN TOTAL ASSET TURNOVER (TATO) TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Faridatul Umay Lira; Lita Permata Sari; Triska Dewi Pramitasari (Fakultas Ekonomi dan Bisnis, 2026)
With stock price acting as an intervening variable, this study attempts to examine the effects of Return on Equity (ROE), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on Company value. The food and beverage firms listed on the Indonesia Stock Exchange (IDX) between 2022 and 2024 are the subject of this study. This study employed purposive sampling and sampled 12 companies. The data analysis tool used in this study was smart PLS 3.0. The data analysis methods included classical assumption tests, consisting of multicollinearity and normality tests, coefficient of determination tests, structural equation analysis (Inner Model), and hypothesis testing. The findings from the direct effect hypothesis test indicate that Return on Equity (ROE) has a negative but insignificant effect on stock price; Debt to Equity Ratio (DER) also has a negative but insignificant effect on stock price; and Total Asset Turnover (TATO) has a positive but insignificant effect on stock price. Return on Equity (ROE) demonstrates a positive and significant effect on firm value. The Debt to Equity Ratio (DER) has a negative but insignificant impact on firm value. Total Asset Turnover (TATO) has a significant positive impact on firm value. Stock price has a positive but insignificant impact on firm value. Meanwhile, the results of the indirect effect hypothesis test indicate that Return on Equity (ROE) and Debt to Equity Ratio (DER) simultaneously have a negative but insignificant impact on firm value through stock price; while Total Asset Turnover (TATO) has a positive but insignificant impact on firm value through stock price.